Bioeconomy approaches in the European context - Steliana Rodino (Agrarian Economy and Rural Development - Trends and Challenges. International Symposium. 13th Edition, 2022)
Against the background of the scarcity of fossil resources and the reduction of the availability of agricultural land, the emergence of climate change and the growth of the world population, it has become necessary to design sustainable and efficient strategies from the point of view of resource management, in order to ensure the prosperity of future generations. These strategies need to include integrated concepts across multiple sectors and levels of activity. Such a concept is considered bioeconomy. The present work represents a review of the definition of the bioeconomy in European states, the evolution of the concept and the variety of existing approaches. It will be demonstrated that the bioeconomy represents an emerging sector that is based on the creation, development and revitalization of economic systems based on a sustainable use of renewable biological resources, in a balanced way. The bioeconomy has evolved from an almost esoteric concept to becoming the core of development strategies at regional and national as well as local levels. It has also permeated the sphere of interest of the scientific and technological communities and financial and economic and industrial circles. It should be emphasized that the bioeconomy does not represent a new industry or economic sector, but a combination of production-processing sectors and final markets that are characterized by the use of renewable resources, natural resources, ecological technologies and efficient recycling.
Keywords: A1; A12; Q57; 330; bioeconomy; strategy; sustainable development; agriculture; biotechnology